Addition of exogenous sodium palmitate increases the IAPP/insulin mRNA ratio via GPR40 in human EndoC-βH1 cells. (3rd July 2017) - Krizhanovskii, Camilla; Fred, Rikard G.; Oskarsson, Marie E.; Westermark, Gunilla T.; Welsh, Nils
Abstract: Background: Enhanced IAPP production may contribute to islet amyloid formation in type 2 diabetes. The objective of this study was to determine the effects of the saturated fatty acid palmitate on IAPP levels in human β-cells. Methods: EndoC-βH1 cells and human islets were cultured in the presence of sodium palmitate. Effects on IAPP/insulin mRNA expression and secretion were determined using real-time qPCR/ELISA. Pharmacological activators and/or inhibitors and RNAi were used to determine the underlying mechanisms. Results: We observed that EndoC-βH1 cells exposed to palmitate for 72 h displayed decreased expression of Pdx-1 and MafA and increased expression of thioredoxin-interacting protein (TXNIP), reduced insulin mRNA expression and glucose-induced insulin secretion, as well as increased IAPP mRNA expression and secretion. Further, these effects were independent of fatty acid oxidation, but abolished in response to GPR40 inhibition/downregulation. In human islets both a high glucose concentration and palmitate promoted increased IAPP mRNA levels, resulting in an augmented IAPP/insulin mRNA ratio. This was paralleled by elevated IAPP/insulin protein secretion and content ratios. Conclusions: Addition of exogenous palmitate to human β-cells increased the IAPP/insulin expression ratio, an effect contributed to by activation of GPR40. These findings may be pertinent to our understanding of the islet amyloid formation process.